Visual, Verbal and Everyday Memory 2 Years After Bariatric Surgery: Poorer Memory Performance at 1-Year Follow-Up - Walø-Syversen, Gro; Kvalem, Ingela L.; Kristinsson, Jon; Eribe, Inger L.; Rø, Øyvind; Brunborg, Cathrine; Dahlgren, Camilla Lindvall (Frontiers in Psychology, 2021)
Severe obesity has been associated with reduced performance on tests of verbal memory in bariatric surgery candidates. There is also some evidence that bariatric surgery leads to improved verbal memory, yet these findings need further elucidation. Little is known regarding postoperative memory changes in the visual domain and how patients subjectively experience their everyday memory after surgery. The aim of the current study was to repeat and extend prior findings on postoperative memory by investigating visual, verbal, and self-reported everyday memory following surgery, and to examine whether weight loss and somatic comorbidity predict memory performance. The study was a prospective, observational study in which participants (n = 48) underwent cognitive testing at baseline, 1 year and 2 years after bariatric surgery. Repeated measures analyses of variance revealed significantly poorer visual and verbal memory performance at the 1-year follow-up, with performance subsequently returning to baseline levels after 2 years. Verbal learning and self-reported everyday memory did not show significant postoperative changes. Memory performance at 1 year was not significantly predicted by weight loss, changes in C-reactive protein levels or postoperative somatic comorbidity (Type 2 diabetes, sleep apnea, and hypertension).The study demonstrated poorer visual and verbal memory performance at 1-year following surgery that returned to baseline levels after 2 years. These findings are in contrast to most previous studies and require further replication, however the results indicate that postoperative memory improvements following bariatric surgery are not universal. Findings suggest that treatment providers should also be aware of patients potentially having poorer memory at 1 year following surgery.